THE CHAOS THEORY AND POLITICAL ANALYSIS: THROUGH THE PRISM OF THE UNPREDICTABILITY OF POLITICAL EVENTS - Asiyat Kazievna Botasheva (Современная наука и инновации)
In political analysis, determinism and the perception of complex systems as ordered are not losing their positions. But in the political space, the isolated existence of a nonlinear deterministic system is impossible, since external or internal interference will always interfere, which leads to distortion of the trajectory of various states and functions. The property of unpredictability is increasingly becoming a property of politics at all levels and scales of the event field. We can talk about special systems of the third type (complexity), for which a deterministic-stochastic paradigm is relevant in conducting political analysis. The study of the specific properties and differences of these special systems of the third type (complexity) from traditional deterministic or stochastic systems determine the necessity of introducing the uncertainty principle for such special systems. Chaos is not accidental - it is the eternal companion of all dynamic systems, and the more complex the system, the more valuable is the deterministic-stochastic paradigm.